Fractional-order describing function of systems with backlash - Barbosa, Ramiro (2019)
This paper analyses the dynamical properties of systems with backlash and impact phenomena based on the describing function method. It is shown that this type of nonlinearity can be analysed in the perspective of the fractional calculus theory.